Virtual inertia control to active support of the variable-speed wind turbine in variable frequency limit time - Tingyun, Gu; Houyi, Zhang; Bowen, Li; Junyi, Mao; Qiang, Fan; Yutao, Xu; Qihui, Feng (Frontiers in Energy Research, 2024)
Constraining the virtual inertia of variable-speed wind turbines within the variable frequency limit time will be the key to improve the wind power's reliability of supporting the system frequency actively. Firstly, this paper analyzes the controllable characteristics and evaluation methods of virtual inertia of wind turbine. Secondly, quantify the variable frequency limit time of the grid with highproportion wind power, and consider the wind turbine speed and power margin to restrict the virtual inertia of the wind turbine during the period of frequency drop or rise, so as to provide reliable inertia support to ensure the safety of the system frequency. On this basis, analyze the inertia demand under the frequency safety of the system, and proposed the virtual inertia control strategy of variable-speed wind turbine in the variable frequency limit time by using the speed tracking performance of wind turbine. Finally, the grid with high-proportion wind power simulation system is built to verify that the variable-speed wind turbine can reliably satisfy the inertia demand of system frequency modulation under the proposed control strategy, and significantly improve its active support performance to the power grid.